Solvothermal synthesis of Fe-C codoped TiO2 for visible-light photocatalytic degradation of emerging organic contaminants - Shi, Wenyang. (2011)
In this study, a highly visible-light photoactive Fe-C codoped TiO2 was synthesized using a solvothermal method. The effects of Fe content and calcination temperature were evaluated. The prepared samples were characterized by various techniques, including X-ray diffraction, Brunauer-Emmet-Teller analysis, UV-vis spectroscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, photoluminescence spectroscopy and transmission electron microscopy. It is observed that the crystal size, surface area and crystal morphology were strongly influenced by calcination temperature as well as doping content of iron. The Fe-C codoped TiO2 is of anatase phase, with well-developed mesoporosity and a large BET surface area (149.5 m2 g-1). The phase transformation from anatase to rutile occurred at the calcination temperature of 600 °C. Moreover, the Fe-C doped TiO2 exhibited effective separation of photo-induced electrons and holes compared to those of C-doped and Fe-doped TiO2.